Analysis of Articles on Labioplasty with Science Mapping Technique - Esra Comert (Genel Tıp Dergisi)
Objective: Labiaplasty is the surgical reduction of the labia minora. Labiaplasty has become increasingly popular in recent years. The aim of this study is to analyze the studies on labiaplasty in the literature with the science mapping technique. Materials and Methods: The data used in this study were obtained from the Web of Science Core Collection, Scopus and PubMed databases, which contain abstracts and references from high quality and effective scientific articles. The dataset is assembled using the Python programming language and the underlying Pandas library. The obtained data were analyzed with Biblioshiny in R-Studio. Results: The results of the analysis made on the basis of the countries of the responsible authors of the studies on labiaplasty show that the USA is ahead with a total of 85 articles according to the number of articles. Gemma Sharp is the author with the highest number of articles with 19 articles in terms of total number of articles. The source that publishes the most articles on labiaplasty is the Aesthetic Surgery Journal with 58 articles. Conclusion: In our article, the subject of labiaplasty has been analyzed in terms of science mapping, which is the most interesting subject of the last period. It is considered that this study, which is frequently encountered in the literature, will shed light on the studies in its field.